Etiopathogenesis, diagnosis, and approaches to the treatment of arterial hypertension: an assessment of the physicians’ basic knowledge. Final results of the PHYSTARH project - Roman A. Bontsevich (IP Morozov P.V., 2021)
Introduction. Arterial hypertension (AH) is a syndrome accompanied by an increase in systolic blood pressure (BP)140 mmHg and/or diastolic BP90 mmHg. It is a progressive pathology that affects the adult employable population and leads to the development of deadly complications.